Polszczyzna cieszyńska XIX wieku w kazaniach Józefa Schimki - Raclavská, Jana (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
Protestant sermons in Cieszyn Silesia constitute a rich source for the study of the language used in this area in the religious sphere. It is a regional variety of Polish, containing archaisms, dialectisms or words taken from Czech, which were most often given the sound form of the folk dialect of the time. The article presents an analysis of two texts written in the first half of the 19th century by Józef Franciszek Schimko, a pastor in Nawsie/Návsí (today’s Czech Rep.). Franciszek Schimko, son of Cieszyn pastor Samuel Schimko, left behind a rich legacy of sermons in Polish. The Museum of Protestantism in Cieszyn houses his manuscripts of Sunday and funeral sermons. The sermons written in Polish demonstrate a relatively high level of mastery of the Polish language of the time, especially in terms of inflection and word formation. However, his texts contain many elements typical of the language of the Cieszyn population, strongly associated with their everyday speech. The influence of the Czech language is also evident, especially in the area of vocabulary.